A study of profile of patients attending district disability rehabilitation centre at Ballari city - Raghavendra, Bellara; ARB, Sameena; Goud, T. Gangadhara; Basavaraj, S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Over a billion people, about 15% of the world’s population have some form of disability. Rates of disability are increasing due to population ageing and increase in chronic health conditions among other causes. There is paucity of data on the patterns of disability in Ballari district. Methods:A descriptive hospital based study was conducted at disability rehabilitation centre (DRC), Vijayanagara Institute of Medical Sciences, Ballari, Karnataka. The data related to patients with disability on socio-demographic, patterns of disability and etiological variables was collected from patients records maintained at DRC, Ballari, where in data of 388 patients was collected from the previous two years i.e. from 2012 to 2014. Results: More than two thirds of the patients were males (68%) and remaining 32% were females. 45% of them were in the age group of 15-30 years. Commonest disability was locomotor (77.3%) followed by hearing (11.6%), mental (9.3%), visual (5.9%) and speech (3.8%). Lower limb (72.7%) was the commonest organ involved in the occurrence of disability. Majority of them had a disability percentage of 40-75% (76.5%) followed by disability percentage of more than 75% (21.9%) and disability percentage of less than 40% was seen in only 1.5% of patients. Conclusions:Children and young adults were the common groups with disability. Males were more affected than females where the commonest type of disability was locomotor.